The Validity and Reliability Analysis of English National Final Examination for Junior High School - Jayanti, Dwi; Husna, Nida; Hidayat, Didin Nuruddin (Universitas Hamzanwadi, 2019)
The aim of this study is to analyze the validity and reliability of the English National Final Examination for Junior High School academic year 2017-2018. Validity and reliability are two kinds of characteristic to prove whether a test is good or not. This study takes only one sample of test packages from many test packages, because it is considered the test are similar in the content and differ only in the position of test number. This study was taken in one of the private schools in South Jakarta and involved two English subject teachers as validators/ validity analyst. This study was analyzed by using a descriptive method. Content validity was analyzed by comparing the test material in the syllabus to the test item, while the construct validity was analyzed by comparing the graduation standard to the test item. Furthermore, the reliability was analyzed by using Kuder-Richardson Formula (KR20-KR21). The findings of this study show that, the English National Final Examination for Junior High School academic year 2017-2018 fulfilled the criteria of validity and reliability. The content validity shows 92% valid, the construct validity shows 92 % valid, and the reliability shows coefficient 0,784, which means reliable. To conclude, the English National Final Examination for Junior High School academic year 2017-2018 has fulfilled the criteria as a good test.